Influence of cassava variety and storage on gari quality - Almazan, A.M. (1992)
Gari, a partially gelatinized dry cassava meal, was prepared from 35 cassava clones and evaluated to determine whether there are varietal quality differences. Based on the analyses of variance of the various physiochemical parameters measured, swelling capacity in water at room temperature and in water initially at 90-95øC, crude fibre concentration, gari pH, and eba pH and stickiness were significantly different among the gari samples. Swelling capacity was influenced by crude fibre and protein contents, gel consistency in water and in KOH, and amylograph consistency of the paste. Storage of gari with moisture content of ó 10 '#percent#'in sealed plastic bags at 25ñ 2øC for periods ranging 2-40 weeks resulted in decreased cyanide concentration and less eba stickiness.